The effect of work stress and job satisfaction on turnover intention at PT BFI finance Tbk Cikupa Tangerang Sector - Karsikah Karsikah; Ahmad Ghoni (International Journal of Applied Finance and Business Studies, 2026)
This study aims to analyze the effect of Work Stress and Job Satisfaction on Turnover Intention in employees. The method used in this study is a quantitative survey of employees working across several PT companies. BFI Finance Cikupa Tangerang. Data were collected through questionnaires and analyzed using multiple linear regression to test the proposed hypotheses. The results showed that Work Stress did not have a significant effect on Turnover Intention, with a significance value of 0.862. In contrast, Job Satisfaction was shown to have a strong negative influence on Turnover Intention, with a significance value of 0.000. In addition, the analysis showed that the combination of Work Stress and Job Satisfaction significantly influenced Turnover Intention, with a significance value of 0.000. These findings indicate that increased Job Satisfaction can reduce employees' intention to leave the company, while Work Stress needs to be managed in a broader context. This research makes an essential contribution to human resource management in designing strategies to retain employees and improve work well-being.